A simple mathematical method to estimate ammonia emission from in-house windrowing of poultry litter. Issue 6 (12th May 2018) - Ro, Kyoung S.; Szogi, Ariel A.; Moore, Philip A.
ABSTRACT: In-house windrowing between flocks is an emerging sanitary management practice to partially disinfect the built-up litter in broiler houses. However, this practice may also increase ammonia (NH3 ) emission from the litter due to the increase in litter temperature. The objectives of this study were to develop mathematical models to estimate NH3 emission rates from broiler houses practicing in-house windrowing between flocks. Equations to estimate mass-transfer areas form different shapes windrowed litter (triangular, rectangular, and semi-cylindrical prisms) were developed. Using these equations, the heights of windrows yielding the smallest mass-transfer area were estimated. Smaller mass-transfer area is preferred as it reduces both emission rates and heat loss. The heights yielding the minimum mass-transfer area were 0.8 and 0.5 m for triangular and rectangular windrows, respectively. Only one height (0.6 m) was theoretically possible for semi-cylindrical windrows because the base and the height were not independent. Mass-transfer areas were integrated with published process-based mathematical models to estimate the total house NH3 emission rates during in-house windrowing of poultry litter. The NH3 emission rate change calculated from the integrated model compared well with the observed values except for the very high NH3 initial emission rate from mechanically disturbing the litter to form the windrows. This approach can be used to conveniently estimate broiler house NH3 emission rates during in-house windrowing between flocks by simply measuring litter temperatures.